Camp Swift Fire Experiment 2014: SODAR measurements - Bret W. Butler (19657573) (2025)
This data publication contains measurements from a Sound Detecting and Ranging (SODAR) unit collected as part of a prescribed fire research campaign conducted at the Camp Swift Military Base in Bastrop County, Texas on January 15, 2014. The Camp Swift Fire Experiment 2014 consisted of three fires ignited in burn blocks of dimensions 100 meters (m) by 100 m on January 15, 2014. Fires were ignited on relatively flat areas of grass vegetation in moderate winds. A Sound Detecting and Ranging (SODAR) unit gathers wind speed and directionality from the sound waves, initially emitted by the SODAR to the atmosphere, that are reflected by the air flow above the unit. Prior to the day of ignition fuels were cleared around the SODAR to reduce damage from fire. These data were recorded from an Atmospheric Research & technology, LLC model VT-1 profiler SODAR system installed on the western edge of the burn blocks, in the middle of burn block 2. The unit collected vertical profile data prior to, during and after each of the burns. The SODAR provided 10-minute averages of wind direction, and speed at 10-m vertical intervals from 30-m to 250-m. Signal dropout with these data appeared to occur at 110-m and above. Included in this data publication (\Supplements\InstrumentSpecifications.pdf) is a document that contains more information on the instrument specification and accuracies. The objective of the research burns was to create a dataset comprised of ground based and remote sensing measurements. Data gathered by these instruments showed wind behavior at the western boundary of the burn blocks before, during and after the burns. The placement of fire instrumentation also supplemented the data gathered by the wind instruments inside the burn blocks and the anemometers deployed around the burn blocks. This dataset was intended to be part of a larger data set encompassing multiple wind height measurements from two additional SODAR, two ten-meter wind towers, and Unmanned Aerial Vehicle (UAV) wind instrumentation. The data from these additional instruments could not be integrated, analyzed and published to date due to issues with data collection and documentation. These wind measurements were conducted, specifically, onsite in order to document the local wind environment prior to, during and after the burns. Little is understood currently about the quality and quantity of wind instrumentation required for prescribed burns. Specifically, further analysis of these wind measurements might provide information regarding the magnitude of instrumentation required for simple scenarios and relatively flat environments such as occurred at the Camp Swift research burns. Also, wind measurements contained in this dataset portray ambient wind conditions around the time of the burns that might facilitate the development of model inputs. This dataset contains SODAR wind measurements from 30-m to approximately 140 m above the instrument. A summary of the Camp Swift project can be found in the full data download (\Supplements\ CampSwiftFireExperiment2014_Project_Overview.pdf). A United States Forest Service ArcGIS Online interactive website is also developed to describe the study and examine the integrated data quality for the Camp Swift effort (see cross reference below). Finally, a document detailing the procedures used to set up the burn blocks can be found in the full data download (\Supplements\CampSwiftFireExperiment2014_BurnBlockDesign.pdf).